Hypoglycemic Potential of Aqueous Extracts of Ageratum Conyzoides L., Anthocleista Djalonensis A. Chev. and Bidens Pilosa L., Three Plants from the Ivorian Pharmacopoeia - Gnagne, Arthur Stephane; Coulibaly, Kiyinlma; Fofie, N’Guessan Bra Yvette; Bene, Kouadio; Zirihi, Guede Noel (European Scientific Journal, ESJ, 2018)
Ageratum conyzoides L. (Asteraceae), Anthocleista djalonensis A. Chev. (Gentianaceae) and Bidens pilosa L. (Asteraceae) are three plants used in traditional medicine to treat diabetes. The objective of this present study was to investigate the hypoglycemic potential of the aqueous extracts of these three plants, in order to justify their use by traditional healers. Each extract and both control substances were administered at a single dose to animals by gavage using a catheter for each concentration (70, 90 and 110 mg / ml), at the recommended dose (2 ml / 100g of b.w). The search for the hypoglycemic effect of the aqueous extract of each plant in normal glycemic rats given orally showed a decrease in blood glucose. The aqueous extract of Bidens pilosa induces a significant dose-dependent hypoglycaemia. The phytochemical study has revealed the presence of polyphenols, flavonoids, tannins (catechins and gallic), saponosides and alkaloids, compounds with multiple medical properties, including glycemic regulation in diabetics. The study revealed that the aqueous extracts of the three plants have a hypoglycemic potential with the aqueous extract of Bidens pilosa showing better activity, the results of our investigation justify their use in traditional medicine in the treatment of diabetes.